2019
DOI: 10.18415/ijmmu.v6i2.551
|View full text |Cite
|
Sign up to set email alerts
|

Accrual Earnings Management and Real Earnings Management: Increase or Destroy Firm Value?

Abstract: This study aims to investigate empirically the effect of accrual earnings management and real earnings management on firm value. The analysis technique used is multiple linear regression analysis. The research samples were manufacturing firms listed on the Indonesia Stock Exchange during the period of 2013 to 2017. The analysis tool used is Multiple Linear Regression. The test results showed that accrual earnings management measured by discretionary accruals did not affect on value of the firm. Real earnings m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 13 publications
6
28
0
10
Order By: Relevance
“…A small number of studies identify the positive role of DAC in signaling future performance (Robin & Wu, 2015;Dechow et al, 2019;Darmawan et al, 2019;Chen & Gong, 2019). These studies focus in particular on the impact of DAC on investor decisions, by reference to the stock market.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies identify the positive role of DAC in signaling future performance (Robin & Wu, 2015;Dechow et al, 2019;Darmawan et al, 2019;Chen & Gong, 2019). These studies focus in particular on the impact of DAC on investor decisions, by reference to the stock market.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gill et al (2013) concluded the more intense the practice of earnings management, the greater the adverse effect on Indian firms' return on assets. Darmawan et al (2019) also indicated that real earnings management harms manufacturing firms' value on the Indonesia Stock Exchange from 2013 to 2017. In Nigeria, Okafor et al (2018) realized that earnings management and corporate value are correlated negatively.…”
Section: Earnings Management and Corporate Performancementioning
confidence: 99%
“…So far, some research has been done on the impact of earnings management on corporate financial performance (Tabassum et al 2013;Gill et al 2013;Mehrani and Noruzi 2015;Rodriguez-Ariza et al 2016;Sayari and Omri 2017;Okafor et al 2018;Darmawan et al 2019;Khuong et al 2019;Abbas and Ayub 2019;Mostafa 2020;Zhang and Ayisi 2020;Dakhlallh et al 2020;Nobakht and Acar 2021), while some others have focused on the relationship between related party transactions and firm value (Cheung et al 2006;Xiao and Zhao 2009;Kohlbeck and Mayhew 2010;Pozzoli and Venuti 2014;Tambunan et al 2017;Fazli 2019;Hendratama and Barokah 2020;Ashrafi et al 2020), each of which has had different results for various reasons. This gap is fully felt in the research literature to simultaneously examine the effects of earnings management as well as related party transactions on corporate financial performance during a financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Darmawan et al (2019), manajemen laba dapat terjadi ketika manajer menggunakan valuasi dan menyusun transkasi untuk merubah laporan keuangan sehingga beberapa pihak salah mengartikan performa ekonomi perusahaan atau mempegaruhi perjanjian kontrak yang tergantung pada angka akuntansi. Toumeh dan Yahya (2019) menjelaskan setidaknya tujuh teknik popular dalam manajemen laba, yaitu:…”
Section: Manajemen Labaunclassified
“…Manajemen laba yang menjadi acuan adalah manajemen laba akrual atau metode pencatatan akuntansi dan manajemen laba riil yang berasal dari aktivitas operasi perusahaan. Kedua pendekatan tersebut menunjukkan bahwa terdapat peran manajerial yang ingin mengatur laba menjadi lebih tinggi atau lebih rendah untuk kepentingan memberi sinyal yang baik terhadap prinsipal (Darmawan et al, 2019). H2: Manajemen laba memengaruhi persistensi laba di industri transportasi di Indonesia.…”
Section: Manajemen Laba Dan Persistensi Labaunclassified